IMAGES AND PLOTS OF HISTORY OF THE COSSACKS IN WORKS OF HISTORIANS OF THE FIRST HALF OF XIX с. (V. D. SUKHORUKOV, A. M. TURENKO) - O. N. Shevtsova (Гуманитарные и юридические исследования)
Works of the Russian historians of the first half of the XIX century had a number of signs of similarity to works of fiction. In particular, one of such signs was that the plot reminded a literary work plot. Such plots could be found in works on stories of the Cossack troops, the Don V. D. Sukhorukov's army and Black Sea army of A. M. Turenko. The plots in these works reveal such relevant subject lines as the start, the climax and the denouement. In Sukhorukov's work on stories of Don the internal conflict which is not typical of Turenko's work on the Black Sea history can be accurately traced. In these historical works literary plots are characterized by witticism which makes them interesting for the reader.